Effectivity of soap nuts extract (Sapindus rarak) as bioherbicide toward the growth of Leptochloa chinensis and Fimbristylis milacea (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pujisiswanto H, Mar’ah DL, Sriyani N, Yusnita, Evizal R. 2022. Effectivity of soap nuts extract (Sapindus rarak) as bioherbicide toward the growth of Leptochloa chinensis and Fimbristylis milacea. Biodiversitas 23: 1222-1230. Fimbristylis miliaceae and Leptochloa chinensis weeds were grown predominantly in rice fields which cause a decrease in production yields of up to 36%-43%. The aim of this experiment was to evaluate the method of extractions and find the best concentration of Sapindus rarak by Aqueous and methanol extracts against the growth of F. miliacea and L. chinensis, which do not reduce the growth of rice. Two experiments were arranged for this research; the first was bioassay tests of weed growth of F. miliaceae and L. chinensis at the greenhouse, which were applied by aqueous and methanol S. rarak extracts. It was carried out using a randomized block design in factorial (2x5). The second experiment was the rice growth toxicity test which was applied S. rarak extracted by aqueous and methanol, analyzed to single factor randomized design with various concentrations. The results showed that the application of S. rarak extracted by aqueous and methanol was able to inhibit the growth of L. chinensis and F. mileacea weeds at a concentration of 25%, 50% and 75%. The application of S. rarak extracted by aqueous did not affect rice growth, whereas S. rarak extracted by methanol inhibited rice height and stover weight at a concentration of 75%, but did not inhibit root length growth and leaf number.